UPAYA PENINGKATAN KUALITAS KINERJA PELAYANAN KESEHATAN APARATUR SIPIL NEGARA (STUDI IMPLEMENTASI PELAYANAN KESEHATAN DI PUSKESMAS KARANGMALANG KABUPATEN SRAGEN) - Dhani Nuravianto Aji; Asianto Nugroho; Sapto Hermawan (Jurnal Komunikasi Hukum, 2022)
This article aims to determine the efforts to improve the quality of ASN health service performance and the obstacles faced in improving the performance of health services at Karangmalang Health Center, Sragen Regency. This article uses a descriptive qualitative empirical research method with a sociological juridical approach. In this research, the writer took the research location in Karangmalang Public Health Center, Sragen Regency. Based on the results of the benchmark research, efforts to improve the quality of ASN health service performance at the Karangmalang Health Center, Sragen Regency are considered good and satisfactory with the observed variables of health service quality dimensions, namely (1) Tangibles (physical evidence), (2) Reliability (reliability), (3) Responsiveness (responsiveness), (4) Assurance (assurance), (5) Empathy (empathy). The quality of ASN services, theoretically there are five factors to measure the quality of health services. There are several weaknesses that need to be addressed and improved in an effort to improve the quality of ASN health service performance at the Karangmalang Health Center, namely: 1. The dimension of responsiveness in health services is good, only a lack of dentists. This is not in accordance with Permenkes Number 75 of 2014, so that the service for patients with toothache is hampered. 2. Limited stock of generic drugs that are affordable by the community. 3. There is no recruitment of co-assistant staff and intensive doctors, but only accepts students from the nursing department.